2009
DOI: 10.1111/j.1600-0854.2009.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Induced ER Stress: Synergistic Effects of Sterols and Saturated Fatty Acids

Abstract: Stress within the endoplasmic reticulum (ER) induces a coordinated response, namely the unfolded protein response (UPR), devoted to helping the ER cope with the accumulation of misfolded proteins. Failure of the UPR plays an important role in several human diseases. Recent studies report that intracellular accumulation of saturated fatty acids (SFAs) and cholesterol, seen in diseases of high incidence, such as obesity or atherosclerosis, results in ER stress. In the present study, we evaluated the effects of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
219
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(231 citation statements)
references
References 58 publications
7
219
1
Order By: Relevance
“…Figure 2b shows that reduction of lon protease expression did not induce ER stress. In contrast, treatment with cholesterol and palmitate, known inducers of ER stress, did trigger ER stress [18,19] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 97%
“…Figure 2b shows that reduction of lon protease expression did not induce ER stress. In contrast, treatment with cholesterol and palmitate, known inducers of ER stress, did trigger ER stress [18,19] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 97%
“…Data have recently emerged showing that an excess of SFAs and cholesterol induces ER stress (27)(28)(29). In addition, Pineau and colleagues reported that ER stress induced by SFAs and sterols could be rescued by 4-phenyl butyrate, a molecular protein-folding chaperone (30). Furthermore, it has been shown that membrane sterols (which can themselves induce ER stress) inhibit protein translocation across the ER membrane (31).…”
Section: Discussionmentioning
confidence: 99%
“…We (19) and others (26,27) have demonstrated that cholesterol accumulation in the ER membrane triggers ER stress and activation of the UPR in cultured macrophages. Accumulating evidence reveals that ER stress is a cross-point to link cellular processes with multiple risk factors that exist in all stages of AS (10) and believed to play a critical role in lipid metabolic disorder (28), activation of inflammatory reactions (29), and cellular apoptosis (30). Activation of ER stress pathways is also a characteristic of lipid-laden macrophages in both early and advanced atherosclerotic lesions and is proposed to play a role in plaque vulnerability and acute cardiac death (13,26,31), while reduction of ER stress in macrophages alleviates AS in mice (14,15).…”
Section: Discussionmentioning
confidence: 99%